Vpliv stikov in mešanja kultur na kulturno krajino skozi perspektivo migracij - Milharčič-Hladnik, Mirjam (Etnolog. Nova vrsta (Ljubljana), 2016)
The article is based on the historical overview of the impact of migrations on the cultural and linguistic complexity of the Slovenian space since the middle ages. The framework of the article are the implications of the spontaneous nationalistic discourse (methodological nationalism), which enable us to ignore and deny the historical contacts of cultures and people, and the traces that they left and are still leaving on the cultural landscape and its inhabitants on the social and intimate level of identity. The article presents examples of the emigration movements on the Slovenian territory and the impact on the cultural landscape and the culture of mixedness as is presented in the selected museums of the three cultural landscapes: SMO Museum in Špeter, Museum of Civilization of Istria, Reka and Dalmatia in Trst, and Gotscheer Museum in Srobotnik. The aim of the article is also to mention "emigrated" cultural landscape in the places where emigrants settled and constructed it as an imaginary reality.
Keywords: emigration; izseljevanje; immigration; priseljevanje; migracije; migrations; human migration; cultures in contact; kulturni stiki; metodološki nacionalizem; culture of mixedness; methodological nationalism; Slovenija; Slovenia